2012
DOI: 10.1093/ndt/gfs500
|View full text |Cite
|
Sign up to set email alerts
|

Translocation of dendrin to the podocyte nucleus in acute glomerular injury in patients with IgA nephropathy

Abstract: An increasing number of dendrin-positive nuclei in the glomeruli suggest acute glomerular injury in IgAN. Apoptotic podocytes were detectable in the urine of IgAN. It appears that the translocation of dendrin to the podocyte nuclei enhances podocyte apoptosis in acute glomerular injury and leads to podocytopenia in patients with IgAN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 45 publications
2
27
1
Order By: Relevance
“…The IF studies were executed as described previously [20]. After incubation, PTECs on the cover glass of the 12-well culture plates were washed three times with 100 μL of phosphate-buffered saline (PBS) at a pH of 7.4.…”
Section: Methodsmentioning
confidence: 99%
“…The IF studies were executed as described previously [20]. After incubation, PTECs on the cover glass of the 12-well culture plates were washed three times with 100 μL of phosphate-buffered saline (PBS) at a pH of 7.4.…”
Section: Methodsmentioning
confidence: 99%
“…reduction of the absolute number per glomerulus and increase of the glomerular surface area covered by one podocyte, are related to disease progression in patients with IgA nephropathy. Thus, podocyte injury may provide additional prognostic information in these patients [13]. …”
Section: Iga Nephropathymentioning
confidence: 99%
“…My colleagues Kodama and Asanuma et al [13] investigated the existence of nuclear dendrin and the relationship between relocation of dendrin to the podocyte nucleus and disease progression in patients with IgA nephropathy. A positive correlation was observed between acute extracapillary changes and the number of dendrin-positive nuclei per glomerulus.…”
Section: Iga Nephropathymentioning
confidence: 99%
“…It has been suggested that translocation of dendrin (a protein whose function is still unclear) into the nucleus results in apoptosis and loss of podocytes [65,66]. In addition to the translocation of dendrin, downregulation of anti-apoptotic Bcl-2 in podocytes has been associated with elevated serum creatinine, a decline in creatinine clearance, and an increase in proteinuria in IgAN [67].…”
Section: Podocyte-specific Biomarkersmentioning
confidence: 99%